Modern Approaches to Integrated Assessment of Public Health in Russian Federation and the Republic of Kazakhstan - D. N. Begun; E. V. Bulycheva; A. N. Duisembayeva; E. L. Borshchuk; D. S. Omarova (Здоровье мегаполиса, 2024)
Public health management plays an important role in Russian healthcare system. However, the task is impossible without an integrated assessment. In order to understand modern approaches to integral assessment of public health as well as to develop effective methods for its determination, it is necessary to systematize the existing research data. Countries of vast geographical extent, such as Kazakhstan, are of particular interest, as their regional peculiarities do not allow to elaborate a unified approach aimed at improving public health.The purpose was to analyze the scientific research findings on integrated assessment of public health in the Russian Federation and the Republic of Kazakhstan.Material and methods. A keyword search of scientific data available in eLibrary.RU, PubMed, Google Scholar scientometric databases, subsequent study and analysis were carried out. As a result, 35 articles were included in the review for further analysis.Results. In the scientific literature, there is ambiguity in the choice of criteria for an integrated assessment of public health. The use of different approaches and public health indicators reveals the complexity and multilevel nature of the phenomenon. The revealed weight contributions of various public health indicators, as well as the change in their role in different regions, age groups and other cohort groups indicate the need to adapt unified and standardized approaches using correction factors taking into account the above factors. The existing scientific groundwork on integrated assessment of public health in Russian Federation and the Republic of Kazakhstan allows us to predict an upcoming appearance of scientific research that will contain the results of the most accurate and adequate integrated assessment of public health.Conclusion. A comprehensive assessment of public health is a complex multi-level system that should be measured by integral indicators. In this regard, in order to improve these indicators, it is necessary to clarify the criteria characterizing the high indicative value and coverage of various aspects that determine the level of public health.